Hemodynamics, functional state of endothelium and renal function, platelets depending on the body mass index in patients with chronic heart failure and preserved systolic function. - Kushnir, Yu. (Medicni Perspektivi, 2014)
The aim of the study was to evaluate hemodynamics, endothelium function of kidneys and platelets depending on the body mass index (BMI) in patients with chronic heart failure (CHF) and preserved systolic function. 42 patients (mean age - 76,69±0,83 years) with CHF II-III FC NYHA with preserved systolic function (LVEF>45%) were enrolled. Echocardiography was performed, endothelial function, serum creatinine levels and microalbuminuria were determined in patients. BMI and glomerulation filtration rate were calculated by formulas. The morphological and functional status of platelets was estimated by electronic microscopy. It was defined that increased BMI in patients with CHF and preserved systolic function determines the structural and functional changes of the myocardium and leads to the endothelial and renal functional changes. An increased risk of thrombogenesis was established in patients with overweight and obesity.